Edukasi Entrepreneur Fundamental Bagi Siswa SMA N 1 Petang - A. A. Gede Adi Mega Putra; A. A. Istri Ita Paramitha; I Gst. Agung Pramesti Dwi Putri; Ni Kadek Sri Mas Dwayani (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Amid current technological advancements, rapid economic growth through entrepreneurship presents opportunities for the younger generation. These skills should be taught in high school to prepare students for global challenges. The